The Aβ‐clearance protein transthyretin, like neprilysin, is epigenetically regulated by the amyloid precursor protein intracellular domain. (12th March 2014) - Kerridge, Caroline; Belyaev, Nikolai D.; Nalivaeva, Natalia N.; Turner, Anthony J.
Abstract Proteolytic cleavage of the amyloid precursor protein (APP) by the successive actions of β‐ and γ‐secretases generates several biologically active metabolites including the amyloid β‐peptide (Aβ) and the APP intracellular domain (AICD). By analogy with the Notch signalling pathway, AICD has been proposed to play a role in transcriptional regulation. Among the cohort of genes regulated by AICD is the Aβ‐degrading enzyme neprilysin (NEP). AICD binds to the NEP promoter causing transcriptional activation by competitive replacement with histone deacetylases (HDACs) leading to increased levels of NEP activity and hence increased Aβ clearance. We now show that the Aβ‐clearance protein transthyretin (TTR) is also epigenetically up‐regulated by AICD. Like NEP regulation, AICD derived specifically from the neuronal APP isoform, APP695, binds directly to the TTR promoter displacing HDAC1 and HDAC3. Cell treatment with the tyrosine kinase inhibitor Gleevec (imatinib) or with the alkalizing agent NH4Cl causes an accumulation of 'functional' AICD capable of up‐regulating both TTR and NEP, leading to a reduction in total cellular Aβ levels. Pharmacological regulation of both NEP and TTR might represent a viable therapeutic target in Alzheimer's disease. <boxed-text content-type="graphic" id="jnc12680-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Amyloid precursor protein (APP) intracellular domain (AICD) regulates expression of the amyloid (Aβ)‐degrading enzyme neprilysin (NEP). The Aβ‐clearance protein transthyretin (TTR) is also epigenetically regulated by AICD, derived specifically from the neuronal APP695 isoform. Cell treatment with agents up‐regulating 'functional' AICD increases production of TTR and NEP and reduces Aβ levels which might represent a viable therapeutic target in Alzheimer's disease.